The Relationship Between Self-Concept and Post-Stroke Depression in Stroke Patients - Nisfil Mufidah; Lantin Sulistyorini; Rahmad Wahyudi; Faisal Amir; Sitti Sulaihah; Nova Adila Nur (KHD Production, 2024)
Stroke is when something goes wrong with the blood vessels in your brain, and it can cause serious problems like not being able to move or talk. The are two main types of strokes – one where the blood vessels get blocked (called ischemic) and another where they burst (called hemorrhagic). The blocked kind is more common and happens most often (almost 90% of strokes are ischemic). Meanwhile, hemorrhagic stroke is caused by a leak or rupture of blood vessels in or around the brain, thereby blocking blood flow to brain tissue. Based on preliminary studies, it was found that there was still a high incidence of depression in post-stroke patients at RSU ANNA Medika Madura. The research aims to determine whether there is a relationship between self-concept and post-stroke depression in stroke patients. This research method uses cross-sectional. The independent variable is self-concept, while the dependent variable is post-stroke depression. The total population was 94 stroke patients with a sample of 76 respondents. The sampling technique uses purposive sampling. The instruments used were self-concept questionnaires and HDRS. The statistical test uses the Spearman rank correlation test with a 0.05. The results of the Spearman rank test for the self-concept variable with post-stroke depression obtained a p-value of 0.000 < α 0.05. This research concludes that there is a relationship between self-concept and post-stroke depression in stroke patients. It is hoped that the researchers' suggestions can increase understanding about stroke, improve self-concept to avoid depression.